(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article refers to the particular use dedicated to documentary heritage of Ukrainian writers as an important thematic and aesthetic, ethical areas of their crea-tive achievements on the literature lessons. Memoirs being applied at the lessons of artistic biography, greatly reduces the distance between writer and reader, helps «closely» approach to the author, see him as a man, feel the epoch when an author lived to understand the course of social events.